Analysis of the Practice of Selling and Buying Polyethylene Terephthalate from the Perspective of Ecological Jurisprudence - Syufa'at, Syufa'at; Meidina, Ahmad Rezy; Imani, Firstdina Putri (Journal of Law, Politic and Humanities, 2025)
This paper abstracts a problem one of the problems faced in society today is the problem of waste. Waste not only has an impact on the physical environment, but also has an impact on the non-physical environment, namely the social life of the community such as; cases of landfills (TPAS), degradation of soil and water quality, social conflict. However, waste can be valuable if it is sorted from the time it is generated and becomes raw materials that are awaited by recycling companies, such as paper, plastic, metal, glass companies need glass. Almost all inorganic waste can be sold to companies through collectors so that it can be valued. The research in this article uses field research at PT Planetary Recyled Plastic Indonesia in Banyumas, using the Fikih Ecology approach. The results of data collection were carried out by means of observation, interviews, and documentation. The results of the research in this article show that good and correct waste management not only has an impact on the preservation of the ecosystem of living things, but can also be used as a source of goodness by making it a tool for charity (shodaqoh Sampah)